1972
DOI: 10.1002/pol.1972.150100720
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of 4‐vinylpyridine with acylating agents

Abstract: The reaction of 4‐vinylpyridine (4‐VP) with acylating agents in diethyl ether was investigated. Acetyl chloride (AcCl) and trifluoroacetic anhydride [(TFAc)2O] yield colored oligomers with 4‐VP, denoted P‐4VP—AcCl (III) and P‐4VP—(TFAc)2O (IV). Nuclear magnetic resonance spectrometry was used to analyze these products. A structure (XII), representing a random copolymer resulting from 1,2‐polyaddition and 1,6‐polyaddition to 4‐VP, is proposed for III and IV. Alternative mechanisms which explain these observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Both 2-and 4-vinylpyridine have been reported (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82) to undergo spontaneous polymerization either upon attempted quaternization with alkyl halides or protonation with mineral acids. Further discussion of the extensive mechanistic studies reported on this problem is beyond the scope of this summary (Equation [10][11][12][13][14].…”
Section: Linear Crystalline Polvflthvteniminamentioning
confidence: 99%
“…Both 2-and 4-vinylpyridine have been reported (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82) to undergo spontaneous polymerization either upon attempted quaternization with alkyl halides or protonation with mineral acids. Further discussion of the extensive mechanistic studies reported on this problem is beyond the scope of this summary (Equation [10][11][12][13][14].…”
Section: Linear Crystalline Polvflthvteniminamentioning
confidence: 99%